Survey data on public awareness on the value of marine biodiversity conservation in the Strait of Sicily (Central Mediterranean Sea)Mendeley Data - Evelina Carmen Sabatella; Fabio Fiorentino; Umberto Grande; Valentina Lauria; Danilo Scannella; Germana Garofalo (Data in Brief)
The Strait of Sicily (SoS) is a region of key ecological importance because of its peculiar oceanographic conditions, high biodiversity, and critical role as a transition area between the western and eastern basins of the Mediterranean Sea. The SoS was designated as an Ecologically or Biologically Significant Area (EBSA) by the Contracting Parties of the Convention on Biological Diversity in 2014 [1] and acknowledged as an Important Shark and Ray Area (ISRA) in 2023 [2].Ongoing research and conservation efforts are essential to protect this vital marine corridor from increasing anthropogenic pressures. Public awareness and perception can significantly influence policy development, resource allocation, and the effectiveness of conservation plans. Despite its great importance, surveys to assess society awareness and perception have been rarely implemented in the SoS, in particular from the perspective of marine biodiversity as a provider of valuable ecosystem services.This dataset presents raw data from a survey conducted through in-person interviews between November 2023 and January 2024, yielding 128 responses from 7 locations along the southern coast of Sicily, which borders the northern sector of the SoS. The survey was structured in 4 sections: (1) confidence and awareness about the biodiversity conservation in the SoS; (2) perception about habitat conservation efforts and their level of effectiveness; (3) willingness to pay for habitat conservation in the SoS; and (4) socio-demographic information. Participation was voluntary, responses were anonymous and all respondents provided informed consent after reading a participant information form at the beginning of the survey.This dataset, despite its limited size, is a valuable resource for quantitative analyses, filling a gap in similar analysis in the study area and offering an original perspective focused on biodiversity as an ecosystem service. It provides opportunities for researchers and policymakers to estimate the economic value that individuals place on preserving marine biodiversity. By assessing these valuations, stakeholders can gain insights into the public's willingness to pay for conservation initiatives and their prioritization of different aspects of marine ecosystem preservation.The dataset accompanying this article includes several critical components. It contains a copy of the questionnaire used to gather data, providing transparency and allowing for replication or further study. Additionally, detailed information about the participants is included, which can help understanding the demographic and socioeconomic factors that influence public perception and preferences. The data itself is meticulously compiled, and a corresponding codebook is provided to facilitate accurate interpretation and analysis. This robust documentation ensures that users can efficiently navigate and utilize the dataset for their specific research needs.